Estimation of Accumulated Environmental Damage: Methods and Experience - NOVOSELOVA, Irina Yurievna; NOVOSELOV, Andrey Leonidovich (Journal of Environmental Management and Tourism; Vol 7 No 4 (2016): JEMT Volume VII Issue 4(16) winter 2016, 2017)
The article shows the necessity to make economic estimation of the accumulated damage in order to solve a wide range of the tasks related to management in the area of the environmental protection and ecological rehabilitation of the region. The method of the economic estimation of the accumulated damage that takes into account the period of the negative impact on the environment and absorbing opportunities of the territory is provided. The peculiarities of calculating the accumulated damageare demonstrated. The method of the scenario tree to forecast damages from polluting the environment during the previous periods and to make a probability estimate of the accumulated damage is offered. For longer periods, it is recommended to calculate the accumulated damage based on the theory of fuzzy sets using triangular numbers. The method of economic estimation of the accumulated damage was used in the practice of ecological and economic calculations to stipulate the efficiency of regional programs related to liquidating theaccumulated damage and ecological rehabilitation of regions.